NTRK fusions in colorectal cancer: clinical meaning and future perspective. (3rd August 2021) - Ratti, Margherita; Grizzi, Giulia; Passalacqua, Rodolfo; Lampis, Andrea; Cereatti, Fabrizio; Grassia, Roberto; Hahne, Jens Claus
ABSTRACT: Introduction: Despite the efforts of the scientific community, the prognosis of metastatic colorectal cancer (mCRC) remains poor. Actionable gene fusions such as Neurotrophic Tropomyosin Receptor Kinases (NTRK) rearrangements are rare but might represent a new target to improve outcomes in this setting. The first-generation TRK inhibitors, larotrectinib and entrectinib, have demonstrated efficacy and safety in mCRC cancer patients exhibiting NTRK pathogenic fusions. Moreover, second-generation molecules are emerging, able to overcome the acquired resistance to NTRK blocking. Areas covered: This review aims to report the current knowledge and the available evidence on NTRK fusion in mCRC, with a focus on molecular bases, clinical characteristics, prognostic meaning, and new therapeutic approaches, from the perspective of the clinical oncologist. Expert opinion: Considering the limited options associated with the treatment of mCRC patients, the possibility of identifying new molecular biomarkers is an urgent clinical need. The availability of new molecular targets and the combinations of different agents might represent the true breakthrough point, allowing for change in the clinical course of colorectal cancer patients.